Developing a VR Factory Walkthrough for Use in Schools - Krings, Sarah, Claudia; Yigitbas, Enes; Sauer, Stefan (CCSD, 2024)
Part 5: Demos International audience Practical experiences are an important part of the education in vocational schools. In many cases, for example concerning production modes, this experience is gained by excursions to factories. Since the number of such excursions is limited by time and money constraints, and since the current alternative are traditional, less immersive materials such as books or videos, we present a virtual reality (VR) walkthrough of a demonstration factory. We collected requirements that are specific to this situation, built an application, and evaluated it, according to the human-centred design process. From this, we derive an overview of the special precautions and the challenges related to development for use in a school setting.